Challenges of New Energy Power Systems - Zuo, Jingxu (International Journal of Electric Power and Energy Studies, 2024)
At present, in the context of global energy transition, China is actively promoting the construction of a high-proportion renewable energy power system, but it faces multiple challenges. First of all, the increasing demand for new energy installed capacity and the challenge of power balancing ability make the system operation face complexity and uncertainty. Secondly, the reshaping of market mechanisms and business models, as well as complex challenges at the technical level, are also constraints. The key technologies involved include innovation and application in simulation analysis and mechanism cognition, system construction, energy frame and stability control.